Factors influencing sustainable tourism economic growth: A case study of Lampang Province, Thailand - Amaporn Pongrungsie; Warin Wongwan; Pariyet Sitthisuang; Wutthirat Patthanibool; Autchariya Krautharot; Kamonwat Phuwichit (Kasetsart Journal of Social Sciences, 2025)
This study investigates the factors that influence sustainable economic growth caused by Community-Based Tourism (CBT). Two communities in Lampang province, where the success in applying the Sufficiency Economy Philosophy (SEP) to CBT is evident, are studied. A total of 377 questionnaires were used to obtain the data. The Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach was employed to test the hypotheses. The results of the testing of the measurement model and structural model indicate their reliability. Data analysis indicated that entrepreneurial skills fully mediate the relationship between SEP and sustainable economic growth. This finding holds managerial implications for other communities with similar contexts. Related agencies should enhance the communities’ entrepreneurial skills based on the SEP. This could serve as a driving mechanism toward sustainable economic growth based on the philosophy of sufficiency economy.